Deep‐Blue Light‐Emitting Diodes Constructed with Perovskite Quasi‐2D and Nanocrystal Mixtures. Issue 20 (13th July 2022) - Pang, Peiyuan; Xing, Zhaohui; Xia, Junmin; Wang, Bingzhe; Zhang, Zhipeng; Guo, Jia; Liu, Tanghao; He, Bingchen; Chen, Jiangshan; Chen, Shi; Xing, Guichuan
Abstract: In the past several years, metal‐halide perovskites have attracted much attention for their promising applications in light‐emitting diodes (LEDs). Significant progress has been made in the development of high‐efficiency green, red, and near‐infrared perovskite LEDs (PeLEDs), but blue PeLEDs are still lagging behind. Although the external quantum efficiency (EQE) of blue PeLEDs has exceeded 10%, these works mainly focus on pure blue and sky‐blue regions. Creating deep‐blue electroluminescence (EL) with high stability, efficiency, and color purity is still a great challenge for PeLEDs. Herein, deep‐blue PeLEDs are reported which have been constructed with a mixture of a quasi‐2D phase and a nanocrystal phase by introducing a small diamine cation, ethylene diammonium (EDA 2+ ), and the effect of EDA 2+ on quasi‐2D perovskite crystallization is investigated. EDA 2+ with two amino ending groups has a stronger inhibitory effect on high‐ n phase growth than phenylethyl ammonium, leading to the formation of small nanocrystals. Further introduction of Na + reduces the size of the nanocrystals and broadens the band gap. Based on these improvements, deep‐blue PeLEDs with EL peaks at 467 (EQE ≈ 1.7%) and 461 nm (EQE ≈ 1.1%) are successfully constructed. Thus, this study provides a useful strategy for improving the performance of deep‐blue PeLEDs. Abstract : Deep‐blue perovskite films with a mixture of quasi‐2D phase and nanocrystals are successfully deposited by simultaneously incorporating a small diamine cation and Na + . Tailoring the phase components and promoting the crystallization of nanocrystals enables quasi‐2D perovskite light‐emitting diodes to achieve deep‐blue emission with electroluminescence peaks at 467 and 461 nm, and the color coordinates meet the requirement of CIE y < 0.1.